NUAK Kinases: Brain–Ovary Axis - Ester Molina; Linda Hong; Ilana Chefetz (Cells, 2021)
Liver kinase B (LKB1) and adenosine monophosphate (AMP)-activated protein kinase (AMPK) are two major kinases that regulate cellular metabolism by acting as adenosine triphosphate (ATP) sensors. During starvation conditions, LKB1 and AMPK activate different downstream pathways to increase ATP production, while decreasing ATP consumption, which abrogates cellular proliferation and cell death. Initially, LKB1 was considered to be a tumor suppressor due to its loss of expression in various tumor types. Additional studies revealed amplifications in LKB1 and AMPK kinases in several cancers, suggesting a role in tumor progression. The AMPK-related proteins were described almost 20 years ago as a group of key kinases involved in the regulation of cellular metabolism. As LKB1-downstream targets, AMPK-related proteins were also initially considered to function as tumor suppressors. However, further research demonstrated that AMPK-related kinases play a major role not only in cellular physiology but also in tumor development. Furthermore, aside from their role as regulators of metabolism, additional functions have been described for these proteins, including roles in the cell cycle, cell migration, and cell death. In this review, we aim to highlight the major role of AMPK-related proteins beyond their functions in cellular metabolism, focusing on cancer progression based on their role in cell migration, invasion, and cell survival. Additionally, we describe two main AMPK-related kinases, Novel (nua) kinase family 1 (NUAK1) and 2 (NUAK2), which have been understudied, but play a major role in cellular physiology and tumor development.